Intercultural Dimension of Internationalisation of Higher Education and Intercultural Learning in Formal and Non-formal Education: The Experts’ Views from Italy and Ukraine - Sikorska , Iryna; Pendenza, Massimo; Goncharenko, Mykhailo; Myroshnychenko, Nataliia; Rtyshchev, Serhii (Acta Paedagogica Vilnensia, 2024)
This research seeks to contribute to a deeper understanding of intercultural dimension of internationalisation of higher education and intercultural learning through perception of educators, policy-makers, representatives of civil society sector in Italy and Ukraine. We have attempted to study if internationalisation has operated a shift towards qualitative learning objectives, making universities to focus on intercultural learning within the internationalisation process. For educators the growing presence of debates on intercultural issues has posited a series of challenges on preparing interculturally competent graduates. Methodology used consisted semistructured interviews of the selected experts in both countries. Findings indicate that intercultural dimension of internationalisation can intwine appropriately with the goals of higher education however analysis showed that qualitative outcomes of internationalisation process are rather underestimated at national and institutional levels in both countries. The study underscores the critical importance of integrating intercultural dimensions into the internationalisation of higher education, revealing distinct approaches in Italy and Ukraine, advocating for collaborative efforts between academia and civil society to enhance intercultural awareness and competences, and emphasising the positive potential for a transformative evolution in the future.